Health Care Providers in War and Armed Conflict: Operational and Educational Challenges in International Humanitarian Law and the Geneva Conventions, Part I. Historical Perspective. (30th April 2018) - Burkle, Frederick M.; Kushner, Adam L.; Giannou, Christos; Paterson, Mary A.; Wren, Sherry M.; Burnham, Gilbert
Abstract: Since 1945, the reason for humanitarian crises and the way in which the world responds to them has dramatically changed every 10 to 15 years or less. Planning, response, and recovery for these tragic events have often been ad hoc, inconsistent, and insufficient, largely because of the complexity of global humanitarian demands and their corresponding response system capabilities. This historical perspective chronicles the transformation of war and armed conflicts from the Cold War to today, emphasizing the impact these events have had on humanitarian professionals and their struggle to adapt to increasing humanitarian, operational, and political challenges. An unprecedented independent United Nations–World Health Organization decision in the Battle for Mosul in Iraq to deploy to combat zones emergency medical teams unprepared in the skills of decades-tested war and armed conflict preparation and response afforded to health care providers and dictated by International Humanitarian Law and Geneva Convention protections has abruptly challenged future decision-making and deployments. ( Disaster Med Public Health Preparedness . 2019;13:109–115)